2010
DOI: 10.1007/s12192-010-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

Larval excretory-secretory products from the parasite Schistosoma mansoni modulate HSP70 protein expression in defence cells of its snail host, Biomphalaria glabrata

Abstract: Synthesis of heat shock proteins (HSPs) following cellular stress is a response shared by many organisms. Amongst the HSP family, the ∼70 kDa HSPs are the most evolutionarily conserved with intracellular chaperone and extracellular immunoregulatory functions. This study focused on the effects of larval excretory-secretory products (ESPs) from the parasite Schistosoma mansoni on HSP70 protein expression levels in haemocytes (defence cells) from its snail intermediate host Biomphalaria glabrata. S. mansoni larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 65 publications
2
43
0
1
Order By: Relevance
“…glabrata hemocytes after incubation with excretory/secretory products (ES) from S . mansoni [77], which was linked to a parasite strategy to manipulate the snail’s immune response. Conversely, other studies have described an up-regulation of the expression levels of this protein as a result of parasite infection [34, 36, 78], so the role of these proteins in the snail’s defense against pathogens is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…glabrata hemocytes after incubation with excretory/secretory products (ES) from S . mansoni [77], which was linked to a parasite strategy to manipulate the snail’s immune response. Conversely, other studies have described an up-regulation of the expression levels of this protein as a result of parasite infection [34, 36, 78], so the role of these proteins in the snail’s defense against pathogens is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…2), larvae release a mixture of molecules into the surrounding medium including an array of glycoproteins (Guillou et al 2007; Wu et al 2009). Hemocytes, when exposed to these larval transformation products (or LTPs; Wu et al 2009), exhibit altered in vitro motility, phagocytic activity, and capacity to encapsulate sporocysts (Bayne 2009; Yoshino and Coustau 2011) as well as modulation of specific proteins (e.g., HSP70; Zahoor et al 2010) that are associated with schistosome resistance in snails (Ittiprasert et al 2009; Ittiprasert and Knight 2012). To better understand how LTPs interact with snail cells at the molecular level, Bge cells were treated with LTPs of S. mansoni and Echinostoma caproni Richard, 1964 and transcript expression was evaluated.…”
Section: Molluscan Cell Linesmentioning
confidence: 99%
“…Additionally, unlike the Lockyer et al study where constitutive expression of Hsp 70 transcript was not observed in either resistant or susceptible adult snails, we showed that the expression of Hsp 70 occurs at similar levels in both normal resistant and susceptible juvenile snails. Furthermore, another study done using hemocytes collected from parasite exposed adult resistant and susceptible snails, showed down regulation of the Hsp 70 protein occurs in hemocytes of both these snails following infection, with more suppression of the transcript in susceptible than in resistant adult snails [23]. Thus, from the above studies, it is clear that there are major discrepancies concerning the expression of Hsp 70 between juvenile and adult resistant and susceptible snails, either with, or without infection, and also from hemocytes removed from infected adult resistant and susceptible snails.…”
Section: Introductionmentioning
confidence: 97%